Animal Welfare Attitudes: Effects of Gender and Diet in University Samples from 22 Countries - Christoph Randler; Ana Adan; Maria-Mihaela Antofie; Arturo Arrona-Palacios; Manecas Candido; Jelle Boeve-de Pauw; Priti Chandrakar; Eda Demirhan; Vassilis Detsis; Lee Di Milia; Jana Fančovičová; Niklas Gericke; et al. (Animals, 2021)
Animal Welfare Attitudes (AWA) are defined as human attitudes towards the welfare of animals in different dimensions and settings. Demographic factors, such as age and gender are associated with AWA. The aim of this study was to assess gender differences among university students in a large convenience sample from twenty-two nations in AWA. A total of 7914 people participated in the study (5155 women, 2711 men, 48 diverse). Participants completed a questionnaire that collected demographic data, typical diet and responses to the Composite Respect for Animals Scale Short version (CRAS-S). In addition, we used a measure of gender empowerment from the Human Development Report. The largest variance in AWA was explained by diet, followed by country and gender. In terms of diet, 6385 participants reported to be omnivores, 296 as pescatarian, 637 ate a vegetarian diet and 434 were vegans (n = 162 without answer). Diet was related with CRAS-S scores; people with a vegan diet scored higher in AWA than omnivores. Women scored significantly higher on AWA than men. Furthermore, gender differences in AWA increased as gender inequality decreased.